Empathy in Youths with Conduct Disorder and Callous-Unemotional Traits - Annarita Milone; Luca Cerniglia; Chiara Cristofani; Emanuela Inguaggiato; Valentina Levantini; Gabriele Masi; Marinella Paciello; Francesca Simone; Pietro Muratori (Neural Plasticity, 2019)
Previous studies indicated that a lack of empathy could be considered the core feature of callous-unemotional (CU) traits in children and adolescents. The present study is aimed at exploring relationships among CU traits, cognitive and emotional dimensions of empathy, emotion recognition (basic, social, and complex emotions), and history of maltreatment in a sample of youths with conduct disorder diagnosis. The sample consisted of 60 Italian male patients (age range 11-17 years, mean age 13.27±1.90 years) referred to the Department of Child and Adolescent Psychiatry (Pisa, Italy). In the whole sample, the levels of CU traits were significantly negatively associated with both cognitive and emotional dimensions of empathy; in addition, the CD patients with high levels of CU traits show significantly lower levels of empathic concern compared to those with low levels of CU traits. Clinical implications of the findings are discussed.